Efektivitas pembelajaran online basic life support terhadap peningkatan kemampuan penanganan kegawatdaruratan prehospital pada mahasiswa keperawatan di Kota Langsa - Zulkarnaini Zulkarnaini; Nora Hayani; Elfida Elfida (Poltekkes Kemenkes Aceh, 2024)
Background: An emergency is a dangerous situation that can cause disability or even death. Efforts can be made to provide basic life support to prevent injury or death of victims. The training aims to enable students to handle the correct handling of emergencies to save the victim.Objective: To measure the effectiveness of basic life support online learning on improving the ability to handle pre-hospital emergencies in nursing students in Langsa City.Methods: This quantitative study used a quasi-experimental design through a pre-test and post-test approach with a control group. The sample size was 50 people who were divided into two groups. The intervention group was carried out online learning while the control group was given a video tutorial. Data were collected using questionnaires and pre and post training practice tests. Data analysis used Dependent T-test and Independent T-test at 95% CI.Results: The results of the study in the intervention group and control group were that there were significant differences in the ability to handle pre-hospital emergencies of respondents (p = 0.000), and the ability of respondents (p = 0.000), and the online learning method of basic life support through zoom was better than learning through video tutorials (p = 0.000).Conclusion: Online basic life support training is more effective in improving prehospital emergency management skills than video training.